Association of polymorphism of CYP3A4, ABCB1, ABCC2, ABCG2, NFKB1, POR, and PXR with the concentration of cyclosporin A in allogeneic haematopoietic stem cell transplantation recipients. (3rd July 2021) - Wang, Linlin; Zeng, Guangting; Li, Jianqiang; Luo, Jia; Li, Huilan; Zhang, Zanling
Abstract: Cyclosporin a (CsA) was characterized by a narrow therapeutic window and high interindividual pharmacokinetic variability. In this study, we aimed to identify the association of CYP3A4, ABCB1, ABCC2, ABCG2, NFKB1, POR, and PXR polymorphisms with CsA concentrations in patients with allogeneic haematopoietic cell transplantation (allo-HSCT) based on the route of administration. A total of 40 allo-HSCT recipients receiving CsA were genotyped for CYP3A4, ABCB1, ABCC2, ABCG2, NFKB1, POR, and PXR polymorphisms. The correlation between polymorphisms and CsA concentration was analysed. The CsA dose-adjusted trough concentration (Cssmin/D) of oral or intravenous administration was significantly different ( p  < 0.001). For CsA Cssmin/D of intravenous administration, CYP3A4 rs2246709 ( p  = 0.015), ABCC2 rs717620 ( p  = 0.024), ABCG2 rs2231142 ( p  = 0.042), PXR rs3732359 ( p  = 0.008), PXR rs3814058 ( p  = 0.028) and PXR rs6785049 ( p  < 0.001) had a significant effect on CsA Cssmin/D. For CsA Cssmin/D of oral administration, ABCC2 rs717620 ( p  = 0.009) and ABCG2 rs2231142 ( p  = 0.011) had a significant effect on CsA Cssmin/D. These results illustrated that the CYP3A4, ABCC2, ABCG2, and PXR genotypes were closely correlated with CsA Cssmin/D, suggesting these SNPs were suitable for determining the appropriate dose of CsA.